Study on change of some characters and morphology of polyethylene compound exposed naturally in Dong Hoi-Quang Binh - Minh, Le Duc; Chinh, Nguyen Thuy; Thu Trang, Nguyen Thi; Giang, Nguyen Vu; Trung, Tran Huu; Huynh, Mai Duc; Giang, Le Duc; Hoang, Thai (Vietnam Journal of Chemistry, 2016)
The degradation and stability of high density polyethylene (HDPE) compound depend strongly on geographic, weather and climatic factors (solar radiation, temperature, humidity, etc.). From June 2014 to June 2015, the samples of HDPE compound were tested naturally on outdoor shelves in Dong Hoi sea atmosphere region (Quang Binh province) for evaluation of change of their morphology and properties. The tensile property results show that tensile strength and elongation at break of HDPE compound reduced significantly while their Young modulus rose as increasing natural testing time. After 12 months of exposure, the tensile strength and elongation at break of HDPE compound decreased 47.63% and 1.39% in comparison with unexposed HDPE compound, respectively. Scanning Electron Microscopy (SEM) analysis on the surface of HDPE compound shows the number of cracks and size of cracks of the samples increase and the cracks become bigger and deeper when increasing natural exposure time. The thermo gravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicate that the thermal stability of HDPE compound steadily declines versus natural exposure time. Keywords. HDPE, photo-degradation, natural exposure, tensile property, thermal property, morphology